2015 International Joint Conference on Neural Networks (IJCNN) 2015
DOI: 10.1109/ijcnn.2015.7280613
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular N-terminal domain suffices to discriminate class C G Protein-Coupled Receptor subtypes from n-grams of their sequences

Abstract: Abstract-The investigation of protein functionality often relies on the knowledge of crystal 3-D structure. This structure is not always known or easily unravelled, which is the case of eukaryotic cell membrane proteins such as G Protein-Coupled Receptors (GPCRs) and specially of those of class C, which are the target of the current study. In the absence of information about tertiary or quaternary structures, functionality can be investigated from the primary structure, that is, from the amino acid sequence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In previous research, we also analyzed whether the extracellular N-terminus domain of the sequences sufficed to distinguish between class C GPCR subtypes [16]. These experiments revealed that, although the classification models built using the isolated N-terminus domain did not achieve the subtype discrimination capabilities of the entire sequence in full, the observed reduction of classification performance was not too significant.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, we also analyzed whether the extracellular N-terminus domain of the sequences sufficed to distinguish between class C GPCR subtypes [16]. These experiments revealed that, although the classification models built using the isolated N-terminus domain did not achieve the subtype discrimination capabilities of the entire sequence in full, the observed reduction of classification performance was not too significant.…”
Section: Introductionmentioning
confidence: 99%
“…In this database, receptors are characterized according to subtype labels at different levels of organization. In previous research [12], the analysis of the N-terminus of the extracellular domain provided some preliminary evidence of the potential use of individual domains of complete class C GPCR sequences as the foundation for subtype classification.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor databases are regularly updated. A class C dataset from March 2011 was object of extensive analysis using ML methods in previous research [3,5,12,121,72].…”
Section: Comparison Of Class C Gpcr Datasets 621 Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations